Evaluation of Measurement Uncertainty Obtained with a Tool Probe on a CNC Machine Tool - Salamacha, Daria; Jozwik, Jerzy (Manufacturing Technology Journal, 2023)
The paper presents the results of measurement uncertainty obtained with a tool probe for 4 cutting tools with different values of the nominal radius rf = {3,4,5,7} mm. The tool probe was used to collect experimental data enabling the evaluation of the uncertainty budget of the measuring system. The evaluation was made based on a statistical analysis of measured tool radius values. Each radius value was determined by 30 repetitions of tool probe measurement. The mean value and the standard uncertainty of obtained results were determined. Assuming that the expansion factor was k=2, the expanded uncertainty U was determined, its value ranging between 0.00142 mm and 0.00462 mm for the tested tool radius values. The standard uncertainty ranged from 0.00081 to 0.00231 mm. According to the manufacturer's specifications, the standard uncertainty of the probe is 0.0015 mm.
Keywords: Tool probe; Measurement uncertainty; Contour tolerance; Dimensional and shape accuracy; CNC machine tool